2017
DOI: 10.21276/ijlssr.2017.3.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Significance of Genus: Impatiens

Abstract: ABSTRACT-The genus Impatiens (Compositae) was reviewed for its chemical constituents and biological significance and its traditional uses. The genus has been known for its various biological activities like: antimicrobial activity, antioxidant activity, antiallergic activity, antipruritic activity, antidermatitic activity, transcriptional activity, anti-rheumatoid arthritis activity, anti-histamine activity, testosterone 5α-reductase inhibitory activity, cyclooxygenase-2 inhibitory activity and anti platelet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Furthermore, flavonoids possess biomolecular activities such as apoptosis rate increase, cell proliferation inhibition, lipid peroxidation inhibition, angiogenesis inhibition, DNA oxidation inhibition (Chahar et al, 2011, Yalcın et al, 2017. Most of the Jurinea species are rich in flavonoids such as sesquiterpene lactones and triterpenes (Shah et al, 2014, Singh et al, 2016, Ayad et al, 2017. In phytochemical studies, Jurinea species have been found to contain flavonoids such as apigenin, catechin, caffeic acid and routine (Shah et al, 2014, Ayad et al, 2017, That known for their anticancer activities in various cancer cell lines (Yin et al, 1999, Wenzel et al, 2000, Chahar et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, flavonoids possess biomolecular activities such as apoptosis rate increase, cell proliferation inhibition, lipid peroxidation inhibition, angiogenesis inhibition, DNA oxidation inhibition (Chahar et al, 2011, Yalcın et al, 2017. Most of the Jurinea species are rich in flavonoids such as sesquiterpene lactones and triterpenes (Shah et al, 2014, Singh et al, 2016, Ayad et al, 2017. In phytochemical studies, Jurinea species have been found to contain flavonoids such as apigenin, catechin, caffeic acid and routine (Shah et al, 2014, Ayad et al, 2017, That known for their anticancer activities in various cancer cell lines (Yin et al, 1999, Wenzel et al, 2000, Chahar et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…J. brevicaulis grows in and around the Anatolian Dialogue, one of the major centers of endemism and considered as the hot spot of biodiversity in Turkey, and widely distributes in Erzincan and Gümüshane provinces ( Figure 1) (Tubives;Dogan et al, 2007;Gemici et al, 2008). Previous studies show that Jurinea species have been used traditionally as aphrodisiac and in the treatment of eye infections, fever, gout and rheumatism (Singh et al, 2016); And have different biological activities as antioxidant and anti-lipid peroxidation (Shah et al, 2014;Taherkhani 2015, Ayad et al, 2017, antibacterial (Dwivedi and Wagay, 2014;Ayad et al, 2017), antifungal and DNA Protection Activity (Singh et al, 2016) and in vitro cytotoxic potential against cancerous cell lines (Taherkhani and Rustaiyan 2016). However, there is no studies evaluate the biological activity of Turkey endemic J. brevicaulis; Therefore, as a preliminary study of antineoplastic activity, the cytotoxicity and the antioxidant activity were evaluated for methanol, water, chloroform and ethyl acetate J. brevicaulis extracts.…”
Section: Jurinea Brevicaulis Is a Plant Belonging To Thementioning
confidence: 99%
“…India has about 4.5 million plant species and among them estimated only 250,000-500,000 plant species, have been investigated phytochemically for biological or pharmacological activity [3] . The bioactive constituents or plants extracts may be uses for treatment of various diseases and these would be used as a new formulation for the novel drugs discovery in pharmaceutical industries [4] . Herbal medicines such as Brahmi and Ashwagandha help boost one's energy level, increase nutrients, restore body cells, and enhance a person's immunity [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The rose balsam Impatiens balsamina L. (Balsaminaceae) is an annual tropical herbaceous plant which in whole or part has been used as traditional medicine (remedies) in Asian countries such as Japan, Korea, China, Taiwan, Thailand, Malaysia and India to treat various ailments [7][8][9][10][11][12][13][14] . Previous pharmacological studies reported promising antipruritic, antidermatitic, antihistaminic, antimicrobial (antibacterial and antifungal), analgesic, antioxidant, anti-inflammatory, anti-rheumatic, anti-anaphylactic, antitumor and anticancer activities from the testings of various I. balsamina extracts, often correlated with higher presence of natural compounds including quinones, anthocyanins, glycosides, alkaloids, saponins, flavonoids/flavanols, phenolics as well as terpenoids 10,[14][15][16][17][18] .…”
mentioning
confidence: 99%